LICENCIATURA EM CIÊNCIAS BIOLÓGICAS: UM ESTUDO SOBRE A FORMAÇÃO PEDAGÓGICA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
This study presents an analysis on the pedagogic training offered in the Degree Course on Biological Sciences of the State University of Northern Paraná- UENP, Jacarezinho/PR campus. This study was based on schoolars such as Bourdieu (1989, 2004), Rosso (2007, 2010), Diniz-Pereira (1999, 2006), Nóvoa (1995), Imbernón (2011), Gimeno Sacristán (1999), Gauthier (1998), Shulman (1986), and others. We understand the teachers training field, particularly concerning the degree course on Biological Sciences, as a social field with specific interests and dispute between biological disciplines and pedagogical disciplines. Therefore, our reflections are grounded on the following objective: a) to discuss the articulation of pedagogical disciplines supported by Education and specific disciplines forming the Degree Course in Biological Sciences; b) to understand how the initial pedagogical training provides teachers with sufficient assistance to exercise their profession. The foundation we bring to discussion on the central concepts of praxeology by Pierre Bourdieu, field and habitus, aiming at establishing a dialectical articulation between individuals and social structures. In order to develop the methodological foundation, we applied the qualitative research, in turn, our considerations and theoretical subsidies were grounded on reflections by Richardson (1999) and Triviños (1987). The data collection was carried out using closed questionnaire answered by seven (7) teachers, semi-structured interview with seven (7) teachers and the coordinator of the Biological Sciences Course. We also conducted a document analysis on the Course Pedagogical Project. The orientation on the process of data analysis presented a discussion carried out by the categories concerning the Content analysis (BARDIN, 1977). The research results indicate that the teachers understand the importance of the initial pedagogical training in a degree course nevertheless they believe that such training offered in the course is not sufficient to offer the foundations for teaching functions. They also point out the presence of dichotomy between biological disciplines and pedagogical disciplines as well as a disarticulation between both áreas and their respective teachers.
Licenciatura in Biological Sciences: a study of pedagogical training.
Keywords: formação de professores; docência; conhecimento pedagógico; teachers training; teaching; pedagogical knowledge; CNPQ::CIENCIAS HUMANAS::EDUCACAO